Needs analysis of speaking skills for Mathematics Education students in academic contexts - Alim, Aprilia Helmiyati; Deliza, Annisa; Tiana, Melly; Pratiwi, Dwiyani; Sukarno (Universitas Negeri Semarang, 2025)
This study explores the English language requirements of Mathematics Education students in academic settings using a qualitative descriptive methodology. The urgency of this study lies in the growing academic demand for non-English major students—particularly those in mathematics and science disciplines—to actively participate in English-medium academic practices such as thesis presentations, seminar discussions, and international collaboration. However, English speaking skills are often overlooked in ESP programs for these learners, resulting in a gap between what is taught and what is needed in the field. Data were gathered through interviews and document analysis involving ten third-semester Mathematics Education students at an Indonesian university. The findings revealed that students require speaking skills primarily for academic presentations, journal article discussions, and seminar participation. Key challenges include lack of confidence, grammatical inaccuracy, limited fluency, and difficulty in pronunciation—particularly of mathematical terminology. Students expressed interest in using digital and authentic academic sources such as YouTube videos, podcasts, and subject-related materials, and they preferred interactive learning environments involving group work and practical speaking tasks such as discussions, presentations, and role-plays. These findings highlight the need for a more contextualized English for Specific Purposes (ESP) program that integrates academic content relevant to students’ disciplines and leverages digital media for increased engagement. The implications for both English for Specific Purposes (ESP) and English as a Foreign Language (EFL) contexts indicate that particularly, a need for specific content-based speaking instruction that meets the academic requirements for students in non-English majors who require English language instruction from a discipline-specific context.